Moonshiner's Gold - Erickson, John R. 1943- (New York : Viking, 2001)
In Canadian, Texas, in 1927, not long after his father's death, Riley and his fiddle-playing grandfather must find a way to save the family ranch from a group of moonshiners and the men behind their operation.
Keywords: Grandfathers -- Fiction; Criminals -- Fiction; Prohibition -- Fiction; Texas -- Fiction